Exacerbation of psoriasis induced by interferon-alpha treatment for melanoma - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2016)
Interferon-alpha is one of the major immune modulating agents used in current oncology practice, including melanoma. We present a case of psoriasis exacerbation induced by INF- in a patient with melanoma.
Keywords: Exacerbation; interferon; melanoma; psoriasis